Nutraceutical and Therapeutic Applications of Squalene - Sumi, E. S.; Anandan, R.; Rajesh, R.; Ravishankar, C. N.; Mathew, Suseela (Fishery Technology, 2018)
Squalene, an isoprenoid molecule present in largequantities in deep sea shark liver oil and in smalleramounts (0.1-0.7%) in palm, wheat-germ, olive andrice bran oils, is well known for its antilipidemic,antioxidant and membrane stabilizing properties.Squalene is a key precursor molecule in thebiosynthesis of vitamins, cholesterol and steroidhormones in animals. In human, presence of thishighly unsaturated hydrocarbon keeps the skinhealthy and protects it from ultraviolet radiationsmediated carcinogenesis. Recently, squalene hasdrawn major attention as high valuable compounddue its potential applications in the field ofpharmacological, cosmetic, and nutraceutical industries.The present review includes a brief descriptionabout the natural sources, properties and applicationsof squalene.